Antioxidative enzyme profiling and biosorption ability of Cupriavidus metallidurans CH34 and Pseudomonas putida mt2 under cadmium stress. (8th July 2013) - Shamim, Saba; Rehman, Abdul
<x xml:space="preserve">Abstract</x> Cupriavidus metallidurans CH34 and Pseudomonas putida mt2 were used as cadmium (Cd)‐resistant and ‐sensitive bacteria, respectively, to study their biosorption ability and their antioxidative enzymes. The minimal inhibitory concentration of C. metallidurans CH34 for Cd was found to be 30 mM, and for P. putida mt2 it was 1.25 mM. The tube dilution method revealed the heavy‐metal resistance pattern of C. metallidurans CH34 as Ni2+ (10 mM)>Zn2+ (4 mM)>Cu2+ (2 mM)>Hg2+ (1 mM)>Cr2+ (1 mM)>Pb2+ (0 mM), whereas P. putida mt2 was only resistant to Zn2+ (1 mM). Under Cd stress, the induction of GSH was higher in C. metallidurans CH34 (0.359 ± 0.010 mM g−1 FW) than in P. putida mt2 (0.286 ± 0.005 mM g−1 FW). Glutathione reductase was more highly expressed in the mt2 strain, in contrast to non‐protein thiols and peroxidase. Unlike dead bacterial cells, live cells of both bacteria showed significant Cd biosorption, i.e. more than 80% at 48 h. C. metallidurans CH34 used only catalase, whereas P. putida mt2 used superoxide dismutase and ascorbate peroxidase to combat Cd stress. This study investigated the Cd biosorption ability and enzymes involved in the Cd detoxification mechanisms of C. metallidurans CH34 and P. putida mt2.